Patterns of observed child participation and proximity to a small group including teachers in Swedish preschool free play - Åström, Frida; Almqvist, Lena (Frontiers in Education, 2022)
The participation of all children in the preschool activities is the main outcome of inclusive Early Childhood Education and Care (ECEC). The current study used the Child Observation in Preschool (COP) to explore the observed participation patterns in free play of a sample of 3–5-year-old Swedish preschool children (N = 453), and to examine the characteristics of the resulting clusters in terms of child and preschool unit characteristics. Based on a series of hierarchical and K-means cluster analyses we identified eight distinct and meaningful clusters that could be ranked from very high to very low observed participation. Four of the clusters indicated average to very high observed participation. Two clusters indicated low to very low observed participation. The cluster displaying low observed participation had a high proximity to a small group including teacher. On average, children in this cluster came from preschool units with significantly more second language learners. The cluster displaying a very low observed participation had a low proximity to a small group including teacher. On average, children in this cluster were significantly more often second language learners, and the children came from units with a significantly higher number of resource staff. No significant differences appeared in the number of children with special support needs across the clusters, although tendencies emerged. The results imply that the children in this sample had a varied degree of observed participation. Two clusters of children appeared to have difficulties participating in free play activities where second language learners and children from preschool units with more second language learners were more common. Preschool teachers need to identify children who participate less in preschool activities and who might benefit from more teacher proximity. Teachers also need to reflect on how their proximity impacts the participation of children differently and on the type of support they provide when being close to the children.